Latent profile analysis and influencing factors of psychological resilience in parents of children with autism - Wang, Chunyu; Shuai, Yi; Wang, Huan; Ma, Zhuang (Frontiers in Psychiatry, 2025)
ObjectiveBased on Kumpfer’s psychological resilience framework, this study aimed to explore the potential categories of psychological resilience among parents of autistic children and to analyze the influencing factors of these categories.MethodsData were collected using a general information questionnaire, the Connor-Davidson Resilience Scale (CD-RISC), the Multidimensional Scale of Perceived Social Support (MSPSS), the General Self-Efficacy Scale (GSES), and the Simple Coping Style Questionnaire (SCSQ). From October 2023 to October 2024, a survey was conducted with 350 parents of autistic children at rehabilitation departments and hospitals in western Liaoning Province. A latent profile analysis was performed to assess the levels of psychological resilience, while univariate analysis, variance analysis, and logistic regression analysis were used to identify factors influencing the latent categories of psychological resilience.ResultsThe latent profile analysis identified three categories of psychological resilience among parents: low resilience – pessimistic vulnerable type (34.8%), moderate resilience – comprehensive type (42.1%), and high resilience – strong tough type (23.1%). Logistic regression analysis revealed that multidimensional perceived social support, general self-efficacy, and coping styles (both positive and negative dimensions) significantly influenced the latent categories of psychological resilience (P < 0.05).ConclusionsThe psychological resilience of parents of autistic children exhibits distinct categorical characteristics. Medical staff should implement targeted and personalized interventions tailored to these categories and their influencing factors to enhance the psychological resilience of this population.